Association between bone characteristics and cardiovascular risk factors among adults in selected urban areas in Selangor, Malaysia - Mohamad Ismuddin, Safarina; Thambiah, Subashini C.; Appannah, Geeta; Samsudin, Intan Nureslyna; Md Said, Salmiah; Yeap, Swan Sim; Zahari Sham, Siti Yazmin; Hew, Fen Lee; Sthaneshwar, Pavai (Malaysian Society of Pathologists, 2023)
Introduction: Cardiovascular disease and osteoporosis (OP) have been shown to have similar risk factors but studies have demonstrated contradictory results with regards to their associations. This study evaluated relationships between bone characteristics and cardiovascular risk factors among adults in selected urban areas in Malaysia. Methods: A cross-sectional study was performed involving 331 subjects between 45-90 years recruited at a health screening programme. Sociodemographic and clinical characteristics were recorded. Biochemical analyses on fasting blood samples and dual energy X-ray absorptiometry scan to determine bone mineral density (BMD) were performed. Results: Increased waist circumference (WC) was protective for abnormal BMD status (osteopenia and OP). Males with increased high-density lipoprotein cholesterol (HDL) were more likely to be osteoporotic. WC, fasting blood glucose (FBG) and triglyceride (TG) were positively associated with BMD at all sites but was gender specific. In contrast, WC was negatively associated with trabecular bone score (TBS) for females but this association became attenuated when adjusted for fat percentage. HDL and MetS were negatively and positively associated with BMD, respectively in males. Conclusion: The cardiovascular risk factors of raised WC, FBG, TG and low HDL were significantly associated with increased BMD with skeletal site and gender specific differences after adjusting for confounders. However, a higher WC was associated with a weaker skeletal microstructure reflected by lower TBS in females driven by fat percentage. A higher BMD was demonstrated among MetS individuals. These findings suggest that adiposity may have a protective effect on BMD.